2016
DOI: 10.5539/jsd.v9n5p55
|View full text |Cite
|
Sign up to set email alerts
|

Success and Success Factors of Domestic Rainwater Harvesting Projects in the Caribbean

Abstract: In the Caribbean, domestic rainwater harvesting (DRWH) projects are being implemented to augment water supplies in water scarce islands and as a no-regret approach to adaptation to climate change. The evaluation of these projects is usually limited to the implementation process i.e. measuring the ability of the project to meet the set deliverables. Factors that are considered are the cost and time specified for the installation of the DRWH systems and the quality of the harvested water. There is seldom a post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…rWh is a broad term that can be used to describe the practice of collecting and storing rainfall runoff. it has been used across a variety of low-, middle-, and highincome settings as well as in a range of varying climates as a solution to issues of water scarcity and inadequate drinking water quality (Gould and Nissen-petersen, 1999;saladin and bohara, 2016;peters, 2016). previous studies have shown that the use of rWh systems as primary sources of drinking water is associated with a reduced risk of diarrhoeal disease in children under five years of age when compared with the use of unimproved sources (Garrett et al, 2008).…”
Section: April 2019mentioning
confidence: 99%
“…rWh is a broad term that can be used to describe the practice of collecting and storing rainfall runoff. it has been used across a variety of low-, middle-, and highincome settings as well as in a range of varying climates as a solution to issues of water scarcity and inadequate drinking water quality (Gould and Nissen-petersen, 1999;saladin and bohara, 2016;peters, 2016). previous studies have shown that the use of rWh systems as primary sources of drinking water is associated with a reduced risk of diarrhoeal disease in children under five years of age when compared with the use of unimproved sources (Garrett et al, 2008).…”
Section: April 2019mentioning
confidence: 99%
“…The project evaluations generally look at the extent to which planned activities have been carried out and the extent to which intended objectives have been achieved. They often provide a lot of information on the direct results of the project, but relatively little on the effects of these actions and the resulting impact (Limousin, 2015;Peters, 2016). Thus, despite the billions of dollars injected into development aid each year, there is very little research on the actual impact of projects on the poor (World Bank, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In some of the small islands in the Caribbean where there is a long history of DRWH, self-supply financing was utilised. DRWH that were developed through self-supply, as observed in some Caribbean islands (Peters 2016), encouraged the incremental improvement of household and community DRWH supply through user investment in steps, which are easily replicable and with technologies which are affordable. In these islands people have responded naturally to the need to improve water supply, in the absence of private sector involvement and government advice and services, and with limited commercial financial resources (Peters, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In analyzing the success of DRWH projects in the Caribbean, Peters (2016) identified the economic factors, particularly, the capital costs of DRWH systems as of highest importance. In Australia, DBais et al (2007) reported that the capital cost of DRWH was 66.27% of the life cycle costs (LCC) at an interest rate of 5%.…”
Section: Introductionmentioning
confidence: 99%